Web-based AHP system - Ayu, Media Anugerah; Al-Azab, Mohammed Fadwa Gamal (IIUM Press, 2011)
This chapter discusses about the development of a web-based multi criteria decision making system which implements Analytical Hierarchical Process (AHP) method in order to give the best decision/choice to decision makers. It is believed that such system will be able to offer more accurate and acceptable result based on a number of criteria and alternatives that the user has provided. The main objective of this chapter is to provide an understanding of how such a system is build and some idea on how actually Analytical Hierarchical Process is being implemented in the system. It is hoped that after reading this chapter, readers will get the general concept and idea on how similar systems work and function in the future.